Associations between asthma and Life’s Essential 8: a cross-sectional study - Jiao Xu; Jianlei Tang (Frontiers in Medicine)
BackgroundAsthma is a serious respiratory disease attributed to multiple factors. The Life’s Essential 8 (LE8), introduced by the American Heart Association, aims to improve and maintain cardiovascular health. However, the correlation between LE8 components and asthma remains unclear. We hypothesized that LE8 is a protective factor against asthma.Materials and methodsMultiple logistic regression analysis, restricted cubic spline (RCS) analysis, and subgroup analysis were used to analyze the data collected from the National Health and Nutrition Examination Survey (NHANES) from 2001 to 2018.ResultsA total of 3,360 participants with asthma were included in the analysis. With all confounders controlled for, LE8 scores were negatively correlated with asthma prevalence (odds ratio (OR) per 10-point increment, 0.85 [95% confidence interval (CI), 0.82–0.88]). Compared to low LE8 scores, moderate and high LE8 scores were associated with reduced asthma risk, with adjusted ORs (95% CIs) of 0.59 (0.51–0.68) and 0.48 (0.39–0.58), respectively. Non-linear correlations were observed between LE8 scores and asthma (p non-linear = 0.01) and between health factor scores and asthma (p non-linear = 0.01). However, a linear dose–response correlation was noted between health behavior scores and asthma (p non-linear = 0.30). Subgroup analysis showed no significant interaction effects (p > 0.05), except in the sex and drinking status subgroups (p for interaction = 0.02).ConclusionAsthma is associated with components of LE8, which warrants further attention and may contribute to reducing asthma prevalence.